2006
DOI: 10.1097/00002820-200607000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Subject Recruitment for Cancer Control Studies in an Adverse Environment

Abstract: Subject recruitment in an adverse environment prompted researchers to identify a novel method to gain a different perspective on the problem. Lewin's Model of Change was used in a post hoc examination of recruitment strategies from 5 cancer control studies of breast or prostate cancer. Based on this evaluation, driving and restraining forces in recruitment were identified. Lessons learned and recommendations are discussed based on this evaluation. Five categories of restrainers were identified from this evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Although a patient is more likely to participate in a study if asked by his or her primary care provider or physician (Loftin et al, 2005), having a physician or other clinic or hospital staff member determine study eligibility and introduce the study to potential participants may be challenging given the patient care responsibilities in a busy clinic or hospital unit. In fact, researchers have indicated that the more work required of physicians, the greater the resistance to assist with a study (Heiney et al, 2006). A number of challenges to and strategies for obtaining gatekeeper buy-in have been identified by others (Northouse et al, 2006;Rose, 2000;Villarruel, Jemmott, Jemmott, & Eakin, 2006).…”
Section: Initial Contact Of Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although a patient is more likely to participate in a study if asked by his or her primary care provider or physician (Loftin et al, 2005), having a physician or other clinic or hospital staff member determine study eligibility and introduce the study to potential participants may be challenging given the patient care responsibilities in a busy clinic or hospital unit. In fact, researchers have indicated that the more work required of physicians, the greater the resistance to assist with a study (Heiney et al, 2006). A number of challenges to and strategies for obtaining gatekeeper buy-in have been identified by others (Northouse et al, 2006;Rose, 2000;Villarruel, Jemmott, Jemmott, & Eakin, 2006).…”
Section: Initial Contact Of Participantsmentioning
confidence: 99%
“…Our experience is consistent with reports from the Pew Internet and American Life Project indicating that the demographic characteristics of Internet users tend to be young, male, White, educated, and from a high socioeconomic status (Lenhart, Horrigon, & Fallows, 2004). When advertisements and flyers are a major mode of recruitment, researchers must keep their research office telephones staffed every day, respond as quickly as possible to all inquiries, and anticipate that a high portion of the calls will be from individuals who do not meet study criteria (Heiney et al, 2006;Loftin et al, 2005).…”
Section: Initial Contact Of Participantsmentioning
confidence: 99%
See 3 more Smart Citations